Does BCG Or MMR Or Routine Vaccination Coverage Protect Against COVID Infection And Mortality In India? - Basavewowdanadoddi Marinaik, Shrinivasa; Bhaskar, Adhin; Chinnaiyan , Ponnuraja; Chandrasekaran , Padmapriyadarsini (National Journal of Community Medicine, 2022)
Background: The routine vaccinations and acquired immunity by other viral infections were believed to be acting as a protective factor against severe COVID-19 outbreaks in some countries. This study is overviewing the relationship of routine BCG, MMR vaccinations and reported MMR disease outbreak with reported COVID-19 infection across the Indian states. Methods: The data on vaccination coverage and respiratory disease infection was obtained from Universal immunization program and Integrated disease surveillance project reports. spearman rank Correlation has been used to assess the relationship of routine vaccination and COVID-19 infection. Results: The result did not find any relationship of routine vaccination with BCG and MMR or exposure to MMR infection on COVID-19 infections in India. Conclusion: The exposure to BCG or MMR vaccination did not have a non specific protection against COVID-19 infection. The results imply that a larger proportion of the Indian population is still vulnerable to COVID-19 infection.